Aplikasi Layanan dan Informasi Akademik Berbasis Chatbot Telegram Menggunakan Natural Language Processing - Qalimaturrahmah, Maulida; Santoso, Dwi Budi (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
In the digital era, technological advances change various aspects of life. One of the significant technological advances is Chatbot technology. In the world of higher education, a problem often experienced by students today is a lack of literacy regarding important information available on faculty websites, because not all students always access the website. With Chatbot technology based on Natural Language Processing using the Rasa framework which is integrated into the Telegram platform, it will make it easier for students to get information more quickly and efficiently. The method for creating this Chatbot is literature study, data collection, data pre-processing, flavor framework, implementation, system testing, and results. The data used in creating the Chatbot was taken from information contained on the faculty website. Modification of the Rasa Framework file with a total of 47 intents and 394 examples, training and testing processes carried out via command prompt and integration of the Chatbot into Telegram via Visual Studio Code. From the test results, the Chatbot that has been integrated into Telegram can be used well, the response given by the Chatbot is correct.